School of D-RAD : An Effort of Deradicalization for Former Terrorism Convict - Ali Masyhar; Muhammad Azil Maskur; Eram Tunggul Pawenang; Nadhira Madania Dimarti; Muhammad Azam (Universitas Negeri Semarang, 2025)
This community service is designed to help “Yayasan Persaudaraan Anak Negeri” (Persadani), a Semarang-based foundation comprised of former terrorism convicts, actively engaged in deradicalization efforts. The main issue that is faced by Yayasan Persadani is that there has not been a systematic program to help them in the deradicalization and social reintegration process. Moreover, the lack of religion-based moderation approaches to support deradicalization caused a challenge in preventing them from returning to the radical networks. Yayasan Persadani also faced the lack of a curriculum that is suitable for the life skills of the members and a continuous psychosocial support. School of D-RAD was offered as a solution to those challenges. The School of D-RAD functions as a training hub for the deradicalization of terrorism ex-convicts, assisting 10 participants in their rehabilitation process. It has 3 main programs which are, Religious Moderation Education, Ideological Rehabilitation, Psychological Support with Social Stigma Reduction, as well as Role-Playing and Anti-Radicalism Educational Games. The output target for this activity are, A publication in accredited national scientific journal; A news report on electronic/mass media; a video report of the activity on youtube; and copyright. The expected outcome of this program includes of the hope that the creation of School of D-RAD will be a place for deradicalization, empowerment, the participant’s increased understanding in the religion moderation values for ex-terrorism convicts.